Induction of anti-tobacco mosaic virus antibodies in mice by rabbit antiidiotypic antibodies (The Rockefeller University Press, 1984)
Conventional rabbit antiidiotypic antibodies were raised against a private rabbit anti-tobacco mosaic virus (TMV) idiotype. These rabbit antiidiotypic antibodies were covalently coupled to lipopolysaccharide and then injected into BALB/c mice. As compared with controls, these mice, which have never seen the antigen, synthesized anti-TMV antibodies that are strongly idiotypically cross-reactive with the starting rabbit idiotype. Monoclonal anti-TMV antibodies were prepared from these mice. Furthermore, xenogeneic or syngeneic antiidiotypic antibodies, raised against these monoclonal anti-TMV antibodies, recognized specifically the rabbit idiotype. Rabbit antiidiotypic antibodies alone can induce the same effects, but the concentration of anti-TMV antibodies is lower.